2015
DOI: 10.1111/aor.12568
|View full text |Cite
|
Sign up to set email alerts
|

A New Absorbable Synthetic Substitute With Biomimetic Design for Dural Tissue Repair

Abstract: Dural repair products are evolving from animal tissue-derived materials to synthetic materials as well as from inert to absorbable features; most of them lack functional and structural characteristics compared with the natural dura mater. In the present study, we evaluated the properties and tissue repair performance of a new dural repair product with biomimetic design. The biomimetic patch exhibits unique three-dimensional nonwoven microfiber structure with good mechanical strength and biocompatibility. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…10,19 ReDuraä is a synthetic poly-Llactide (PLLA) which is produced by electrospinning process. 20,21 From characterizations in this study, TissuDuraä was observed to be a dense-type material which resulted in the greatest density, tensile modulus and strength, but the lowest elongation at break. Although being similarly produced from collagen, DuraGen Plusä has much lower density, tensile modulus and strength (1.99%, 0.04% and 0.15% of TissuDuraä, respectively), but higher elongation at break due to its highly porous structure resulted from the manufacturing process.…”
Section: Discussionmentioning
confidence: 75%
“…10,19 ReDuraä is a synthetic poly-Llactide (PLLA) which is produced by electrospinning process. 20,21 From characterizations in this study, TissuDuraä was observed to be a dense-type material which resulted in the greatest density, tensile modulus and strength, but the lowest elongation at break. Although being similarly produced from collagen, DuraGen Plusä has much lower density, tensile modulus and strength (1.99%, 0.04% and 0.15% of TissuDuraä, respectively), but higher elongation at break due to its highly porous structure resulted from the manufacturing process.…”
Section: Discussionmentioning
confidence: 75%
“…However, sutureless absorbable dura also has its advantages of small patches application in some locations difficult to reach, shorter surgery duration and better histomorphologic outcomes (45)(46)(47). A recent study reported a new absorbable dura made of Poly L Lactic Acid which shows good mechanical properties and represents better anti-adhesive property than NormalGEN in preclinical studies (48). Artificial dura made by novel synthetic substitutes is still the important aspect of future research.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,23,24 Although enveloping the grafts with periosteum appears to be a promising approach, clinical evidence supporting its use in humans to augment tendon-bone healing is still lacking, and donor site morbidity is an inevi- the tendon graft to promote tendon-bone healing. 18,26 In the current study, we selected collagen and PLGA to build up a nanofibrous membrane and act as a biomimetic periosteum to enhance tissue invasion and cell attachments in the tendonbone tunnel interface.…”
Section: Discussionmentioning
confidence: 99%